Technical Oral Presentation Delivery: Qualitative Analysis of Engineering Undergraduates’ Impediments to Effective Oral Presentations in an Engineering Context - Benraghda, Abdelmadjid; Noor Raha, Mohd Radzuan; Zuraina, Ali (University of Nebraska - Lincoln, 2018)
Engineering undergraduates are expected to deliver technical oral presentations on various occasions particularly in university subjects. Engineering undergraduates struggle when they are assigned to deliver technical oral presentations and often they have impediments to deliver oral presentations at tertiary level. The paper reveals prime findings on the technical oral presentation’s impediments faced by the engineering undergraduates in delivering effective presentations. A semi-structured interview was conducted by 12 engineering undergraduates from various engineering faculties in Universiti Malaysia Pahang, Malaysia. Findings of the study revealed that the engineering undergraduates encountered impediments such as when delivering technical oral presentations particularly in terms of presentation skills as well as English as a medium of instruction. In this study, the researchers provided, therefore, suggestions on how to improve the engineering undergraduates’ technical oral presentation skills.